PEMODELAN PETA PROSES BISNIS SEBAGAI UPAYA PENGUATAN REFORMASI BIROKRASI (STUDI PADA PEMERINTAH KABUPATEN GARUT) - Lailla Dwi Yulitasari; Nashihah, Durratun; Fadilah Ramadhani, Eva (Jurnal Inovasi Daerah, 2024)
The Government of Garut Regency has formulated a diagram of working relationships between organizational units as an to strengthen bureaucratic reform. The formulation of the working relationship can be realized through the preparation of a business process map of government agencies. This is also supported by the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Regulation Number 19 of 2018 concerning the Preparation of Government Agency Business Process Maps. This research uses a descriptive qualitative method with a thorough exploration of the preparation of the Garut Regency Government business process map. Data was obtained through interviews with the Organizational Section of the Regional Secretariat of Garut Regency, which is authorized in the preparation of documents and is able to explain the flow of business process maps and their details. The results of the research obtained in the form of a tabulation model of the preparation of the Garut Regency Government business process map document as a reference in carrying out community service activities. Through business process mapping in Government Agencies, it can make it easier for ASN to map activities and the body in charge or responsible for realizing the vision and mission that has been formulated.